Comparative analysis of the effect of internet use on democracy development: a case of Asian political structures. (14th September 2020) - Ryu, SeungEui; Udo, Godwin J.; Bagchi, Kallol K.; Kirs, Peeter J.
This study addresses the relationships among internet use, public demand for democracy (PDD), and democracy development using four East Asian nations based on social cognitive theory (SCT). Specifically, the present study compares how the internet use influences democracy development directly and via public demand for democracy in both developing democracy such as Thailand, Malaysia, China, and comparatively developed democracy such as South Korea. Data for the study comes from Asian barometer surveys. Our results indicate that internet use strongly influences public demand for democracy in all four nations and democracy development is positively influenced by public demand for democracy in all the nations studied. We also find out that the effects of demographics on democracy development (and on internet use) are different in each of the four nations. The results are explained and implications provided.